2020
DOI: 10.1021/jacs.0c10442
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Molecular Sensing and Logic Systems Based on Site-Occupying Effect-Modulated MOF–DNA Interaction

Abstract: Interactions between metal−organic frameworks (MOFs) and nucleic acids are of great importance in molecular assembly. However, current MOF−nucleic acid interactions lack diversity and are normally realized in an uncontrollable manner. Herein, the interaction of zirconium-based MOFs (Zr-MOFs) with nucleic acids is enabled by the formation of Zr−O−P bonds and further manipulated by a phosphate-induced site-occupying effect. Covering Zr ions in clusters of MOFs with phosphates impedes the formation of Zr−O−P bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…In order to analyze the pCRISPR and ssDNA interactions with the NGs, these genetic materials were exposed to varying concentrations of NGs. Quenching of the fluorescence emission of the NGs-porphyrin was expected because of the presence of similar interaction of the Zn(Ca)–O–P bonds as recently shown by Yu et al in the presence of Zr-MOF and ssDNA ( Yu et al, 2020a ). The results of the fluorescence emission spectra showed that after loading the ssDNA on the NGs-porphyrin, the fluorescence emission decayed significantly ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…In order to analyze the pCRISPR and ssDNA interactions with the NGs, these genetic materials were exposed to varying concentrations of NGs. Quenching of the fluorescence emission of the NGs-porphyrin was expected because of the presence of similar interaction of the Zn(Ca)–O–P bonds as recently shown by Yu et al in the presence of Zr-MOF and ssDNA ( Yu et al, 2020a ). The results of the fluorescence emission spectra showed that after loading the ssDNA on the NGs-porphyrin, the fluorescence emission decayed significantly ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…Metal–organic frameworks (MOFs) can be finely tuned to exhibit unique properties by careful design of the metallic units and organic linkers . In particular, the mixed-ligand strategy with multiple building units has been proven to be a viable approach for synthesizing functionally tunable MOFs .…”
mentioning
confidence: 99%
“…Metal−organic frameworks (MOFs) can be finely tuned to exhibit unique properties by careful design of the metallic units and organic linkers. 15 In particular, the mixed-ligand strategy with multiple building units has been proven to be a viable approach for synthesizing functionally tunable MOFs. 16 In contrast to single-ligand MOFs (s-MOFs), mixed-ligand MOFs (m-MOFs) enable multiple functionalities by integration of various ligands and have been broadly applied in different fields.…”
mentioning
confidence: 99%
“…Nanotechnology has offered exciting opportunities in the construction of multiscale logic gate networks from single molecules to customized nanostructures that can process information and realize predetermined functions. [8][9][10] With the rapid development of DNA and RNA nanotechnology, nucleic acid strands and assemblies have provided intriguing strategies for the design and construction of logic devices. For nucleic acid molecules, only approximately 50 atoms (one base pair) are needed to store one 1-bit information, which exhibits outstanding capability potential for miniaturizing information storage devices.…”
Section: Introductionmentioning
confidence: 99%